The female runner: Gender specifics - Lynch, S. L.; Hoch, A. Z. (Clinics in Sports Medicine, 2010)
There has been a tremendous increase in the number of female runners of all ages and abilities in the past 35 years. Women who participate in running and sports are generally healthier and have higher self-esteem. However, unique medical and orthopedic issues exist for the female runner. This article reviews the history of women in sports, physiologic and biomechanic differences between genders, the pregnant runner, knee osteoarthritis, an update on the female athlete triad and the relationship between amenorrhea and endothelial dysfunction associated with athletics.